MRI-visible enlarged perivascular spaces in basal ganglia rather than centrum semiovale was associated with aneurysmal subarachnoid hemorrhage - Yu, Qiuyue; Wang, Haichao; Zhang, Wenyi; Zhang, Xiang; Zhao, Jingjing; Gong, Li; Liu, Xueyuan (Frontiers in Neurology, 2024)
Background The subarachnoid space is continuous with the perivascular compartment in the central nervous system. However, whether the topography and severity of enlarged perivascular spaces (EPVS) correlates with spontaneous subarachnoid hemorrhage (SAH) remains unknown. Based on the underlying arteriopathy distributions, we hypothesized that EPVS in basal ganglia (BG-EPVS) are more closely associated with aneurysmal subarachnoid hemorrhage (aSAH) than other SAH without aneurysm. Methods Magnetic resonance imaging (MRI) scans of 271 consecutive SAH survivors with and without aneurysm were analyzed for EPVS and other markers of imaging data. In the subgroup analysis, we compared the clinical characteristics and EPVS of SAH participants with and without pre-existing known risk factors (hypertension, diabetes, and smoking history) using multivariable logistic regression. Results Patients with aSAH (n = 195) had a higher severity of BG-EPVS and centrum semiovale EPVS (CSO-EPVS) than those without aneurysm (n = 76). Importantly, BG-EPVS predominance pattern (BG-EPVS>CSO-EPVS) only existed in aSAH survivors rather than other SAH without aneurysm. In the subgroup analysis, interestingly, we also found that a high degree of BG-EPVS showed an independent relationship with aSAH in patients without pre-existing risk factors (e.g., hypertension). Conclusion In this cohort study, BG-EPVS predominance pattern was associated with aSAH patients compared with those without aneurysm. Moreover, BG-EPVS still showed a strong association with aSAH survivors without pre-existing vascular risk factors. Our present study suggested the BG-EPVS as a potential MRI-visible characteristic would shed light on the pathogenesis of glymphatic function at the skull base for aSAH.